Average TimeSynch: A consensus-based protocol for clock synchronization in wireless sensor networks - Schenato, Luca; Fiorentin, Federico (Automatica (Oxford), 2011)
This paper describes a new consensus-based protocol, referred to as Average TimeSync (ATS), for synchronizing the clocks of a wireless sensor network. This algorithm is based on a cascade of two consensus algorithms, whose main task is to average local information. The proposed algorithm has the advantage of being totally distributed, asynchronous, robust to packet drop and sensor node failure, and it is adaptive to time-varying clock drifts and changes of the communication topology. In particular, a rigorous proof of convergence to global synchronization is provided in the absence of process and measurement noise and of communication delay. Moreover, its effectiveness is shown through a number of experiments performed on a real wireless sensor network.